VLSI implementation of full adder-subtractor design - Ahmad, Nabihah; Lim, Yoong Kang (Medwell Publications, 2017)
Low power consumption and high performance in Very Large Scale Integration (VLSI) design are the major concerns in order to develop an efficient electronic devices. Addition is commonly used arithmetic operation in most electronic system which requires high performance and low power consumption of full adder circuit. This study aimed to design a low power and high performance full adder-subtractor by using Complementary Metal Oxide Semiconductor (CMOS) technology. Four design approaches of 4 bit Full Adder-Subtractor (FAS) static CMOS FAS with Pass Transistor Logic (PTL) XOR, static CMOS FAS with Transmission Gate (TG) XOR, PTL FAS and TG FAS circuit have been implemented in 90 mn CMOS technology using synopsys galaxy custom designer and compared in term of power consumption, power-delay product and area. PTL FAS able to reduce 27 .7% of overall transistor collllt compared to both conventional static CMOS approach. For the 4 bit FAS design, PTL logic approach able to reduce 37. 78% of area occupied and 27. 78% of transistor collllt compared to static CMOS approaches. TG FAS has the lowest power consumption with 112.81 µW followed by PTL FAS with 133.34 µW, less than both conventional static CMOS approach. Results show that the PTL and TG approaches offer a low area and power consumption with a high performance of full adder-subtractor design.